Analysis of circRNA and miRNA expression profiles in IGF3-induced ovarian maturation in spotted scat (Scatophagus argus) - Li, Zhiyuan; Guo, Yuwen; Ndandala, Charles Brighton; Chen, Huadong; Huang, Chunren; Zhao, Guangwen; Huang, Hai; Li, Guangli; Chen, Huapu (Frontiers in Endocrinology, 2022)
Insulin-like growth factor 3 (IGF3) induces ovarian maturation in teleosts; however, research on its molecular regulatory mechanism remains deficient. Circular RNAs (circRNAs) and microRNAs (miRNAs) are involved in various biological processes, including reproduction. In this study, circRNAs and miRNAs involved in IGF3-induced ovarian maturation were evaluated in spotted scat (Scatophagus argus). In ovarian tissues, we identified 176 differentially expressed (DE) circRNAs and 52 DE miRNAs between IGF3 treatment and control groups. Gene Ontology (GO) enrichment analyses showed that host genes of DE circRNAs and target genes of DE miRNAs were enriched for various processes with a high degree of overlap, including cellular process, reproduction, reproductive process, biological adhesion, growth, extracellular region, cell junction, catalytic activity, and transcription factor activity. Enriched Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways included Cell adhesion molecules, ECM-receptor interaction, Regulation of actin cytoskeleton, Focal adhesion, Cell cycle, Hedgehog signaling pathway, Phosphatidylinositol signaling system, PI3K-Akt signaling pathway, Apelin signaling pathway, Notch signaling pathway, Insulin signaling pathway, and Rap1 signaling pathway. A circRNA-miRNA-mRNA regulatory network was constructed, including DE genes involved in reproduction (e.g., oocyte maturation, oocyte meiosis, and ECM remodeling), such as ccnd2, hecw2, dnm2, irs1, adam12, and cdh13. According to the regulatory network and tissue distribution, we identified one circRNA (Lachesis_group5:6245955|6270787) and three miRNAs (novel_miR_622, novel_miR_980, and novel_miR_64) that may exert regulatory effects in IGF3-induced ovarian maturation in S. argus. Taken together, this study provides novel insight into the molecular mechanisms by which IGF3 functions in ovaries and highlights the effects of circRNAs and miRNAs in reproduction in S. argus.